Institutional holdings and analysts’ stock recommendations - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2006)
Prior studies document that institutional investors outperform the mar- ket. We investigate whether this superior performance is partly derived from institutional investors use of sell-side analysts stock recommenda- tions. First, we find that the quarterly change in institutional ownership is positively correlated with consensus recommendations. After control- ling for other determinants of institutional holdings, the quarterly change in institutional ownership is on average 0.90 percent higher for firms with favorable recommendations than for those with unfavorable recommendations. Second, using large trades to proxy for institutional trading, we find that there are more buyer-initiated than seller-initiated large trades around favorable recommendations and vice versa for unfavorable recommendations. Lastly, we find that the change in institu- tional ownership that is explained by stock recommendations is associ- ated with positive abnormal returns in the future, about 4.2 percent per year. Overall, these results indicate that institutional investors trade upon stock recommendations and that such trading contributes to their superior performance.